HUBUNGAN KOMUNIKASI INTERPERSONAL DAN IKLIM KERJA GURU DENGAN MOTIVASI KERJA GURU DI MADRASAH ALIYAH NEGERI 2 DELI SERDANG - Afwan Halim Lubis (Hijri, 2020)
This study aims to determine: 1) Describe the level of teacher work motivation, 2) Describe the function of interpersonal communication between fellow teachers, 3) Describe the work climate cycle of teachers, 4) Describe the relationship of interpersonal communication and teacher work climate to teacher work motivation at Madrasah Aliyah Negeri 2 Deli Serdang. In this study, the hypothesis is formulated as follows: "There is a significant relationship between interpersonal communication and the work climate of teachers with the work motivation of teachers at Madrasah Aliyah Negeri 2 Deli Serdang, totaling 90 people who were determined using total sampling technique. The method used in this research is quantitative research methods. The instrument was designed in the form of a questionnaire for interpersonal communication variables and teacher work climate on teacher work motivation. The validity of the instrument was tested through content validity and construct validity, which were then tested on 30 respondents outside the research sample. While the instrument reliability test was analyzed with SPSS version 16 with the results of the analysis showing that the three variables were at a high level. Data analysis through correlation techniques. The results of the analysis show that there is a relationship between interpersonal communication and the work climate of teachers with the work motivation of teachers at Madrasah Aliyah Negeri 2 Deli Serdang by 50.7%, this means that they have a high level of relationship. This means that the better the interpersonal communication and the work climate of the teacher, the better the teacher's work motivation.